Economic Contributions of Agricultural, Food Manufacturing, and Natural Resource Industries in Florida in 2006 - Alan W. Hodges; Mohammad Rahmani; W. David Mulkey (EDIS)
FE702, a 16-page illustrated report by Alan W. Hodges, Mohammad Rahmani, and W. David Mulkey, quantifies the magnitude of agricultural, food manufacturing, and natural resource industries' contribution to the economy of Florida in 2006, updating a previous study for 2004. Published by the UF Department of Food and Resource Economics, November 2007.